Peran Fitur dalam Memoderisasi Pengaruh Harga terhadap Keputusan Pembelian Smartphone Iphone - Marendra, I Gede; Aryata, I Made (IPB University, 2025)
The rapid development of technology has led to various smartphone products with competitive features and prices. This study aims to determine the effect of features and prices on purchasing decisions of iPhone smartphones at Halo Store, as well as to test the role of features as a moderating variable. Data were collected through questionnaires distributed to 230 respondents using simple random sampling. Data analysis used Structural Equation Modelling (SEM). The results showed that prices had a significant effect on purchasing decisions (p-value = 0.000), features had a significant effect on purchasing decisions (p-value = 0.000), while features as a moderating variable did not strengthen the effect of prices A on purchasing decisions (p-value = 0.056). The implication of this research highlights that a balanced pricing and product features strategy is essential to improve consumer purchasing decisions.